1999
DOI: 10.1063/1.370143
|View full text |Cite
|
Sign up to set email alerts
|

Amorphization of Zr–Al solid solutions under mechanical alloying at different temperatures

Abstract: The effects of temperature on the amorphization of Zr-Al solid solutions have been investigated by ball milling Zr 100Ϫx Al x powder blends at different temperatures. At low milling temperatures, the Zr-Al solid solutions amorphized under the polymorphic constraint imposed by intensive external forcing. At elevated temperatures, the solid solution and the amorphous phases coexisted in an obvious two-phase region, signaling a transition approaching two-phase metastable equilibrium. The Al concentration needed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Moreover, research has been carried out to study the departure of the Al-Zr system from equilibrium by MA processing [3,11,12]. It has been shown that amorphous phase can be developed on ratios that depend mainly on Zr concentrations on alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, research has been carried out to study the departure of the Al-Zr system from equilibrium by MA processing [3,11,12]. It has been shown that amorphous phase can be developed on ratios that depend mainly on Zr concentrations on alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, MA can promote the formation of intermetallics in the Zr-Al system [7,8] and metastable phases in both Mg-Zr [9,10] and Mg-Al [11][12][13] systems. Most of the work published in the Al-Mg-Zr system has focused on the liquid-processing route [4,[14][15][16][17], and little or no information is available on the processing of nanophase Al-Mg-Zr alloys by MA.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive work has been reported on the Zr-Al alloys regarding amorphisation [4], nano-phase formation [5], formation of several metastable phases [6] and also making zirconium based pressure tubes with aluminium lining [7]. The Zr-Al phase diagram [8][9][10] shows ten intermetallic compounds (IMC) viz.…”
Section: Introductionmentioning
confidence: 99%